2011
DOI: 10.1002/cbic.201000754
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bacterial Membranes: Identification of Pseudomonas aeruginosaD‐Arabinose‐5P Isomerase and NMR Characterisation of its Substrate Recognition and Binding Properties

Abstract: The identification and characterisation of Pseudomonas aeruginosa KdsD (Pa-KdsD), a D-arabinose-5P isomerase involved in the biosynthesis of 3-deoxy-D-manno-oct-2-ulosonic acid and thus of lipopolysaccharide (LPS), are reported. We have demonstrated that KdsD is essential for P. aeruginosa survival and thus represents a key target for the development of novel antibacterial drugs. The key amino acid residues for protein activity have been identified. The structural requirements for substrate recognition and bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…1 H NMR-STD spectra clearly indicate that, in both cases, positions 1 and 3 are the most important for enzyme interactions as previously demon- strated for natural substrates. In addition, STD competitive binding experiments [16] performed in the presence of the natural substrates indicated that compounds 1 and 3 compete for enzyme binding with A5P and Ru5P suggestive of active-site binding by 1 and 3. In the case of compound 3 evaluation of the position 6 contribution to binding was not possible due to the absence of protons at the 6 position.…”
Section: Nmr Experimentsmentioning
confidence: 98%
See 2 more Smart Citations
“…1 H NMR-STD spectra clearly indicate that, in both cases, positions 1 and 3 are the most important for enzyme interactions as previously demon- strated for natural substrates. In addition, STD competitive binding experiments [16] performed in the presence of the natural substrates indicated that compounds 1 and 3 compete for enzyme binding with A5P and Ru5P suggestive of active-site binding by 1 and 3. In the case of compound 3 evaluation of the position 6 contribution to binding was not possible due to the absence of protons at the 6 position.…”
Section: Nmr Experimentsmentioning
confidence: 98%
“…Previous NMR studies of API [16] by our group showed that the acidic phosphate group is fundamental to enzyme binding. In particular, we speculate that a salt bridge between the negatively charged phosphate and a complementary basic residue in the catalytic pocket is the key interaction between substrate and enzyme.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…KdsD, the arabinose 5‐phosphate isomerase catalyzing the first step in the synthesis of Kdo, has also been investigated as a molecular target to design novel antimicrobials . Compounds able to inhibit KdsD activity have been rationally designed based on the available crystal structure of KdsD catalytic domain, and on the determination of KdsD structural requirements for substrate recognition and binding . While able to inhibit KdsD activity in vitro, none of the compounds displayed a significant MIC (minimal inhibitory concentration) against a selected panel of Gram‐negative pathogens, strongly suggesting that these molecules are not able to permeate across the OM.…”
Section: Targeting Lps Biogenesis Pathway For the Discovery Of Novel mentioning
confidence: 99%
“…These components are synthesized in the cytoplasm or in the IM, and are then selectively transported to the OM by specific transport machines. Recent reviews on the transport and assembly systems of OM components have been published with the aim of developing inhibitors targeting these systems [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%